SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JENIS TANAMAN PANGAN BERDASARKAN KANDUNGAN TANAH MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DENGAN ALGORITMA GENETIKA - Yuliani Indrianingsih; Winda Susyanti Naibaho (Institut Teknologi Dirgantara Adisutjipto, 2015)
Samosir regency is a from North Sumatera province which dominantly people is live on agriculture. The most of the farmers using autodidact learning to determining the types of plants that will be process the appropriate with their land, where farmers just learn from their experiences and exchange opinion with another farmers. Based of the problem, the system will be built by Analytical Hierarchy Process (AHP) with Genetic Algorithm. The result of the testing from method Analytical Hierarchy Process (AHP) obtained result with consistency ratio values < 0,1, which is -0,5936 while the result of the testing from Genetic Algorithm obtained value of the fitness is 157,25. Based on the test results, it can be concluded that the method Analytical Hierarchy Process (AHP) obtained the result more consistent with the value of consistency ratio should be < 0,1, so it will be easier to making decision, while on the analysis of Genetic Algorithm, obtained result are probabilistic as always having random process, so that decision making can not be consistent. So, Decision Support System to determination of plants based by contents of soil which are good and suitable is method Analytical Hierarchy Process (AHP).